The miniRAD instrument for the MMX IDEFIX rover - J. Knollenberg; M. Grott; M. Hamm; A. Ihring; R. Ziese; J. Biele (Progress in Earth and Planetary Science)
Abstract The miniRAD radiometer is one of the payloads of the Idefix rover on the MMX mission to Phobos. It is a multispectral instrument which measures the infrared radiative flux in six wavelength channels between 4.7 and 100 µm using single-element thermopile detectors. MiniRAD is equipped with optical filters, one centered at 5.5 µm, three narrow bandpass filters at 8.3 µm, 8.9 µm, and 9.5 µm and two longpass filters with cut-ons at 14–15 µm. One of the longpass filters made from boron nitride (BN) is especially optimized for very low flux, being sensitive in the very long wavelength region even beyond 50 µm. The main measurement objective of the miniRAD instrument is the determination of Phobos’ surface brightness temperature during nighttime, from which the thermal inertia of the surface can be derived. Secondary objectives are to provide constraints on the slope of the emissivity in the thermal infrared, the location of the Christiansen feature, and the surface roughness of Phobos. MiniRAD has been calibrated radiometrically under relevant environmental conditions using a cavity blackbody over the full expected range of object temperatures from 100 to 330 K. The predicted uncertainty of the brightness temperature is < 1 K at dayside temperatures > 270 K for all channels, while the BN filter uncertainty is < 5 K at the lowest calibration temperature of 100 K.